Analysis of The Development Strategy of The Ijen Crater Tourist Attraction, Banyuwangi District - Izdihar Aisy; Alen Ardiansyah; Oktandini Sugesti Putri; Sri Murtini; Ravinesh Rohit Prasad (International Journal of Geography, Social, and Multicultural Education, 2025)
Ijen Crater, located in Banyuwangi and Bondowoso regencies, is a unique and attractive natural tourist destination, famous for natural phenomena such as the deep blue crater lake and rare blue fire. This article discusses the development potential of Ijen Crater as a sustainable tourist destination, focusing on aspects of attractions, facilities and accessibility. Attraction aspects include natural beauty and local culture, such as sunrise views, sulfur miners, and folklore. Existing facilities, although covering basic needs, still need to be improved to support the increasing number of tourists, especially in terms of accommodation, climbing equipment, and educational facilities. Accessibility to Kawah Ijen, while good, could be improved through the development of alternative hiking trails and public transportation. These additions and improvements are expected to enhance the tourist experience and ensure the sustainability of the environment around Kawah Ijen